2018
DOI: 10.1007/s11999.0000000000000244
|View full text |Cite|
|
Sign up to set email alerts
|

Does the Alpha-defensin Immunoassay or the Lateral Flow Test Have Better Diagnostic Value for Periprosthetic Joint Infection? A Systematic Review

Abstract: Level III, diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 17 publications
1
26
0
1
Order By: Relevance
“…One assay is the enzyme-linked immunosorbent assay (ELISA), which is performed in a laboratory with results obtained within 24 h. The second assay is the lateral flow device, which rapidly detects infection within 20 min without the need for a laboratory. Accordingly, pooled results supported the higher sensitivity of the synovial fluid alpha-defensin ELISA compared to the lateral flow test [16,20,23,27] Sonicate fluid and periprosthetic tissue were performed most intraoperatively, whereas tissue PCR and sonicate fluid BCB were the most sensitive tests in tissue and sonicate fluid, respectively. In 2013, Qu et al [37] performed the first meta-analysis of PCR in the diagnosis of PJI.…”
Section: Discussionmentioning
confidence: 61%
“…One assay is the enzyme-linked immunosorbent assay (ELISA), which is performed in a laboratory with results obtained within 24 h. The second assay is the lateral flow device, which rapidly detects infection within 20 min without the need for a laboratory. Accordingly, pooled results supported the higher sensitivity of the synovial fluid alpha-defensin ELISA compared to the lateral flow test [16,20,23,27] Sonicate fluid and periprosthetic tissue were performed most intraoperatively, whereas tissue PCR and sonicate fluid BCB were the most sensitive tests in tissue and sonicate fluid, respectively. In 2013, Qu et al [37] performed the first meta-analysis of PCR in the diagnosis of PJI.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, the most popular diagnostic test applied in recent years was synovial fluid alpha-defensin, which also had the highest sensitivity. Accordingly, pooled results supported the higher sensitivity of the synovial fluid alpha-defensin immunoassay compared to the lateral flow test[14][15][16][17]. Preoperative tests with the lowest sensitivities were synovial fluid gram staining (GS), synovial fluid procalcitonin (PCT), serum white blood cells (WBCs), serum PCT, which were all found to have a sensitivity of less than 60%.…”
mentioning
confidence: 72%
“…The Synovasure kit is a qualitative test with the striking advantage of being a point‐of‐care assay, performed intra‐operatively. However, in addition to being quite expensive, recent meta‐analysis showed that its sensitivity for the detection of PJIs in a real setting is lower than expected, 15–17 possibly due also to the test being performed by untrained personnel. In contrast, the low‐cost HNPs MALDI‐TOF MS assay requires shipping of the sample to the laboratory and is performed by experienced personnel, but still it has a short turn‐around time (TAT; as described above) which is theoretically compatible with an intra‐operative setting, just planning and coordinating the surgery with the clinical laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of meta‐analyses, focused on the different performance of these two analytical methods, have been published. The immunoassay for α‐defensin in SF has been reported to have the highest sensitivity (97.3–100%) and specificity (95.5–100%) compared with other single biomarkers of PJIs, 12,13 whereas the lateral flow test presents a lower sensitivity, ranging from 71% to 92.1%, and specificity from 89% to 100% 15–18 …”
Section: Introductionmentioning
confidence: 99%